Nanofibrillated cellulose causes acute pulmonary inflammation that subsides within a month. Issue 7 (9th August 2018) - Ilves, Marit; Vilske, Sara; Aimonen, Kukka; Lindberg, Hanna K.; Pesonen, Saila; Wedin, Irene; Nuopponen, Markus; Vanhala, Esa; Højgaard, Casper; Winther, Jakob R.; Willemoës, Martin; Vogel, Ulla; et al.
Abstract: Nanofibrillated cellulose (NFC) is a renewable nanomaterial that has beneficial uses in various applications such as packaging materials and paper. Like carbon nanotubes (CNT), NFCs have high aspect ratio and favorable mechanical properties. The aspect ratio also rises a concern whether NFC could pose a health risk and induce pathologies, similar to those triggered by multi-walled CNT. In this study, we explored the immunomodulatory properties of four NFCs in vitro and in vivo, and compared the results with data on bulk-sized cellulose fibrils and rigid multi-walled CNT (rCNT). Two of the NFCs were non-functionalized and two were carboxymethylated or carboxylated. We investigated the production of pro-inflammatory cytokines in differentiated THP-1 cells, and studied the pulmonary effects and biopersistence of the materials in mice. Our results demonstrate that one of the non-functionalized NFCs tested reduced cell viability and triggered pro-inflammatory reactions in vitro . In contrast, all cellulose materials induced innate immunity response in vivo 24 h after oropharyngeal aspiration, and the non-functionalized NFCs additionally caused features of Th2-type inflammation. Modest immune reactions were also seen after 28 days, however, the effects were markedly attenuated as compared with the ones after 24 h. Cellulose materials were not cleared within 1 month, as demonstrated by their presence in the exposed lungs. All effects of NFC were modest as compared with those induced by rCNT. NFC-induced responses were similar or exceeded those triggered by bulk-sized cellulose. These data provide new information about the biodurability and pulmonary effects of different NFCs; this knowledge can be useful in the risk assessment of cellulose materials.